Survivin and inducible nitric oxide synthase production during 4NQO-induced rat tongue carcinogenesis: A possible relationship - Ribeiro, Daniel Araki; Kitakawa, Darcio; Domingues, Maria Aparecida Custódio [UNESP]; Guimaraes Cabral, Luiz Antonio; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier B.V., 2007)
This study was undertaken to investigate, by immunohistochermistry, the expression of survivin and inducible nitric oxide synthase during 4NQO-induced rat tongue carcinogenesis. Male Wistar rats were distributed into three groups of 10 animals each and treated with 50 ppm 4NQO solution through their drinking water for 4, 12, and 20 weeks. Ten animals were used as negative control. Although no histopathological abnormalities were induced in the epithelium after 4 weeks of carcinogen exposure, survivin and iNOS were expresssed (P < 0.05) in some cells of the 'normal' oral epithelium. In pre-neoplastic lesions at 12 weeks following carcinogen exposure, the levels of survivin and iNOS were increased (p < 0.05) when compared to negative control, being the strongest effect observed to iNOS. In well-differentiated squamous cell carcinoma induced after 20 weeks of treatment with 4NQO, survivin and iNOS were expressed in some tumor cells. Lack of immunoreactivity for both markers was observed in the negative control group. Taken together, our results support the belief that expression of survivin and iNOS are early events during malignant transformation and conversion of the oral mucosa. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: survivin; nitric oxide; rat tongue mucosa; oral squamous cell carcinoma; 4-nitroquinoline 1-oxide; malignant transformation